Immobilized Chlorella species mixotrophic cultivation at various textile wastewater concentrations. (December 2020) - Wu, Jane-Yii; Lay, Chyi-How; Chiong, Meng-Choung; Chew, Kit Wayne; Chen, Chin-Chao; Wu, Shin-Yan; Zhou, Dandan; Kumar, Gopalakrishnan; Show, Pau Loke
Highlights: Mixotrophic cultivation of immobilized Chlorella using textile wastewater was examined. Various alginate solutions (0.5–5.0%) for the immobilized technology were studied. Immobilized Wu-G23 with static cultivation showed higher pollutant removal efficiency. Raw textile wastewater (no dilution) resulted in the highest FAMEs accumulation. Abstract: Immobilized microalgae have been utilized for various bioprocesses that yield biofuels and high-value products. Various alginate solutions ranging from 0.5 to 5.0 % were investigated to develop microalgae immobilization technology. High intracellular density (3.94–4.89 g/cm 3 ) and compressive strength (447−602 g) immobilized Chlorella vulgaris Wu-G22 (G22) and Chlorella sp. Wu-G23 (G23) microalgae granules with 3.0 % alginate solution could be obtained after 10 days cultivation using textile wastewater. In addition, effective removal of superfluous biological and chemical pollutants was cultured under mixotrophic conditions for immobilized G22 and G23 using textile wastewater after 7 days. Efficiencies of NH4 + -N, COD and color removal were all greater than 50 % by using immobilized microalgae G23 with static cultivation. The present study confirmed that microalgal/alginate bio-beads/granular are one of the alternatives for defeating microalgae harvesting issues in larger scale production, where the microalgal cells stick to each other on external surfaces.